THE INFLUENCE OF SOCIAL MEDIA MARKETING ON TOURIST VISIT INTENTION TO PARI ISLAND, THOUSAND ISLAND - Adzra Muthi'ah Hafizhah; Beta Budisetyorini; Sumaryadi (Politeknik Pariwisata NHI Bandung, 2022)
One of the government's efforts to increase tourist visits is by doing digital marketing. Digital marketing is also carried out by the SUDINPAREKRAF Thousand Island to increase the number of tourists to Pari Island. Pari Island is one of the resident islands on Thousand Island. Starting from 2018 until now there has been a decline in the level of tourist visits to Pari Island caused to natural disasters. Even so, other resident islands in the Kepulauan Seribu have more tourist visits than Pari Island. In 2020, the SUDINPAREKRAF Thousand Island held technical guidance on using social media as a tool to market Pari Island. This study aims to explain the influence of social media marketing on interest in visiting Pari Island, Thousand Island. This study uses a quantitative approach through a verification method based on probability sampling of the population. The number of respondents in this study was 150 who were obtained through an online questionnaire and were taken according to the target market of the SUDINPAREKRAF Thousand Island. The data obtained were processed using SPSS, interval successive method (MSI), descriptive statistical analysis, and simple regression. The results of this study indicate that social media marketing has a significant effect on interest in visiting Pari Island, Thousand Island.